2017
DOI: 10.3389/fphys.2017.00334
|View full text |Cite
|
Sign up to set email alerts
|

TNFα Modulates Cardiac Conduction by Altering Electrical Coupling between Myocytes

Abstract: Background: Tumor Necrosis Factor α (TNFα) upregulation during acute inflammatory response has been associated with numerous cardiac effects including modulating Connexin43 and vascular permeability. This may in turn alter cardiac gap junctional (GJ) coupling and extracellular volume (ephaptic coupling) respectively. We hypothesized that acute exposure to pathophysiological TNFα levels can modulate conduction velocity (CV) in the heart by altering electrical coupling: GJ and ephaptic.Methods and Results: Heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 53 publications
3
33
0
Order By: Relevance
“…This nanodomain, termed the “perinexus,” is an extracellular space in the intercalated disk directly adjacent to GJ plaques that is narrow (on the scale of 5–30 nm), can be dynamically altered, and contains a high density of the cardiac isoform of the voltage gated sodium channel ( Rhett et al, 2012 ; Veeraraghavan et al, 2015 , 2016 ; Veeraraghavan and Gourdie, 2016 ). Furthermore, we have demonstrated in animal models ( George et al, 2015 , 2016 , 2017 ; Veeraraghavan et al, 2015 ; Entz et al, 2016 ; Veeraraghavan and Gourdie, 2016 ) that altering perinexal width is associated with altered cardiac conduction consistent with the theories of ephaptic coupling ( Kucera et al, 2002 ; Mori et al, 2008 ; Lin and Keener, 2010 ; Hichri et al, 2018 ). While evidence has grown suggesting the importance of non-gap junctional coupling mediating conduction velocity in animal models, it is unknown whether the perinexus can be found in human myocardium, and more specifically the atria.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…This nanodomain, termed the “perinexus,” is an extracellular space in the intercalated disk directly adjacent to GJ plaques that is narrow (on the scale of 5–30 nm), can be dynamically altered, and contains a high density of the cardiac isoform of the voltage gated sodium channel ( Rhett et al, 2012 ; Veeraraghavan et al, 2015 , 2016 ; Veeraraghavan and Gourdie, 2016 ). Furthermore, we have demonstrated in animal models ( George et al, 2015 , 2016 , 2017 ; Veeraraghavan et al, 2015 ; Entz et al, 2016 ; Veeraraghavan and Gourdie, 2016 ) that altering perinexal width is associated with altered cardiac conduction consistent with the theories of ephaptic coupling ( Kucera et al, 2002 ; Mori et al, 2008 ; Lin and Keener, 2010 ; Hichri et al, 2018 ). While evidence has grown suggesting the importance of non-gap junctional coupling mediating conduction velocity in animal models, it is unknown whether the perinexus can be found in human myocardium, and more specifically the atria.…”
Section: Introductionsupporting
confidence: 81%
“…Recent studies suggest that GJs are not the only mechanism for electrical communication between cardiac myocytes. Our research suggests that ephaptic coupling, via the generation of electric fields and ion accumulation/depletion transients within restricted intercalated disk domains, can well describe a number of conduction abnormalities associated with GJ, sodium channel, and ionic modulation ( Veeraraghavan et al, 2012 , 2015 , 2016 ; George et al, 2015 , 2016 , 2017 ; Entz et al, 2016 ).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…CV is determined by the ion channel and cellular interconnections. George et al (2017) demonstrated that TNFα could reduce CV by altering electrical coupling between myocytes in guinea pig hearts. The effects of TNF-α on gap junction coupling have been extensively studied.…”
Section: Tnf-α and Ventricular Arrhythmiasmentioning
confidence: 98%
“…The effects of TNF-α on gap junction coupling have been extensively studied. TNF-α alters Cx43 expression, reduces Cx43 phosphorylation, and alters Cx43 redistribution, which is important in modulating Cx43 channel conductance (Fernandez-Cobo et al, 1999;Sawaya et al, 2007;George et al, 2017).…”
Section: Tnf-α and Ventricular Arrhythmiasmentioning
confidence: 99%